Development of Two‐Channel Phosphorescent Core–Shell Nanoprobe for Ratiometric and Time‐Resolved Luminescence Imaging of Intracellular Oxygen Levels. (4th August 2014) - Sun, Huibin; Zhang, Jie; Zhang, Kenneth Yin; Liu, Shujuan; Liang, Hua; Lv, Wen; Qiao, Weili; Liu, Xiangmei; Yang, Tianshe; Zhao, Qiang; Huang, Wei
<x xml:space="preserve">Abstract</x> An effective strategy is developed to realize a ratiometric oxygen nanoprobe with two‐channel phosphorescence signals based on a core–shell silica nanoparticle. This nanoprobe exhibits good water dispersibility and biocompatibility. Bioimaging experiments demonstrate that the nanoprobe can be used for monitoring the change in intracellular O2 concentration and performing quantitative O2 measurement through ratiometric and time‐resolved luminescence bioimaging. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>